Uncertainties, Employment and the Zero Lower Bound - Nie, Qing; Brown, Xin L.; Liu, Baohui; Morshed, Maruf (International Journal of Energy Economics and Policy, 2024)
The purpose of this paper is to study the response of aggregate and sectoral employment in the United States to shocks and uncertainties in the oil and macro markets. To estimate the actual dataset, we employ a VAR model with 12 variables using U.S. data during 1986Q1-2021Q4. With alternative oil and macroeconomic uncertainties and different monetary authorities, we find that employment is significantly affected by both types of uncertainty when zero lower bound (ZLB) binds. Total employment and oil-related industries employment show a significant increase in the presence of the ZLB and the propagation of uncertainty shock from the oil market. These findings highlight the empirical relevance of oil prices and macroeconomic uncertainty on U.S. labor market dynamics.